(untitled) (KIUT Publication, 2025)
In the era of globalization and international collaboration, English has firmly established itself as the dominant language of global communication. Within this context, English for specific purposes (ESP) and English for academic purposes (EAP) play a crucial role in equipping learners with the linguistic tools necessary for professional and academic success across disciplines. ESP focuses on the development of language skills tailored to specific fields such as engineering, medicine, business, and law, enabling specialists to communicate effectively within their professional communities. EAP, on the other hand, prepares students and researchers to engage with academic discourse, contributing to their ability to publish, present, and participate in global scientific dialogue.